Pengaruh Kualitas Produk, Kualitas Layanan, Dan Lokasi Terhadap Kepuasan Pelanggan (Study kasus pada pelanggan Bp Café) - Jonata, Rizola Ardo Dikri; Wahono, Budi; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2024)
Abstract Product quality is a condition of goods or services being marketed that meet standards or criteria in satisfying customer needs for a good or service. Therefore, product quality is very important in measuring the level of customer satisfaction. Service quality is any action or activity that can be offered by a party to another party which is basically intangible and does not result in any ownership. Furthermore, the location of the Bp Café is located in an alley and the lack of public transportation access to reach this place will make it difficult to find the Bp Café. The location factor is an aspect that needs to be studied, location is a vital aspect in the development of this type of business. The more strategic the business location, the easier it will be for customers to come to visit and make purchases. Customer satisfaction is a feeling of satisfaction or disappointment resulting from a comparison of product performance or results with expectations. Satisfaction itself is a value of pleasure regarding the customer's experience. Keywords: Product Quality, Location, Service Quality, Customer Satisfaction